Three Essays on Crime Deterrence Laws - (:unkn) unknown (My University, 2017)
The main purpose of this dissertation is to apply empirical and theoretical economics methodologies to analyze multiple topics in economics of crime, which have important policy implications. This dissertation consists of three chapters. Chapter 1 introduces new evidence on the impact of concealed carry weapon laws on crime. For more than a decade, there has been an academic debate over the deterrence effect of concealed carry weapon (shall issue) laws. However, all previous studies do not consider the types of gun-carry laws in place prior to the adoption of “shall issue” laws. Using difference-in-difference methodology, the findings of this study imply that considering the type of regulations that states had prior to passing “shall issue” laws matters and “shall issue” laws do have a deterrence effect under certain circumstances. Adopting “shall issue” laws only reduces the crime rate in states with “no issue” laws in place, and “shall issue” laws are redundant to “may issue” (restricted concealed carry) laws in terms of crime reduction. Chapter 2 investigates the deterrence effect of a marginal increase in punishment severity for illegal gun carrying. I explore New York’s 2006 sentence enhancement for illegal gun possession, which effectively added to the sentence for any crime committed with a firearm. Results show that the increase in punishment contributed to the decreasing crime rates in New York after 2006. Chapter 3 investigates the impact of a marginal change in punishment severity on crime rate. I exploit Arkansas’ (AR) 2011 adjustment in the felony threshold for theft from $500 to $1000. The decrease in punishment contributed to an increased theft rates in AR, suggesting criminals responded to the reduced crime-specific cost. Findings also indicate that the likely lower incarceration for theft did not lead to an increase in other crimes.